Model Kontekstual dalam Pembelajaran Listening Children Story dalam Rangka Peningkatan Mutu Proses Pembelajaran (Penelitian Tindakan Kelas di SMPN 10 Depok) - Sarilila Utama (Universitas Indraprasta PGRI Jakarta, 2019)
This research is a classroom action research (CAR) aimed at improving student activity and learning outcomes through the application of contextual approaches to Listening Children Story Learning. The subjects of this study were students of class VIII. B SMP 10 Depok in the academic year 2017/2018, amounting to 35 people. The object of this research is the preparation of student learning, student activities in learning, and student learning outcomes in the learning model applied. The results of this study indicate that the application of contextual learning in listening to children's story learning can improve student learning activities and outcome.